Distribución y observaciones sobre la población de la nutria marina Lontra felina(Molina 1782) en el Perú - Apaza, Manuel (2012)
We analyzed the distribution of marine otter Lontra felinaon the Peruvian coast, from Punta Aguja (05°47'S) to the boundary with Chile (18°21'S). We performed a comprehensive analysis of the literature on L. felinato elucidate a northern boundary of its geographic distribution, concluding that there is no solid evidence of a possible northern limit at 6°S. For the same reasons, the affirmation of a "historic distribution" to the Lobos de Tierra island was discarded. It is also presented information of 272 otters from 130 locations between the years 2000 and 2010. The distribution of these records no has spatial autocorrelation, suggesting a homogeneous distribution. Considering the morphostructure and geomorphology of the Peruvian coast we can see similarities with the division into three zones: north, central and south, the last two add all records of otters, which could provide habitat characteristics that, allow a continuous distribution of L. felina. Finally there is an increase in the number of otters in the Peruvian coast to compare the current values with those of 40 years ago, but we show the lack of traceability of the latest information. We suggest undertaking research linking abundances and densities of otters with the characterization and distribution of their habitats, and behavioral studies that reveal the processes or intrinsic characteristics of the species to move into its geographic range.